Transparency and Accountability Model for Infaq Funds at LAZISNU Kudus - Aflah, Kuntarno Noor; Zuhurul Fukohak, M. Agus; Fitriyati, Arsyada (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2026)
This study aims to determine the transparency and accountability models of donation funds through WhatsApp (WA) notification feedback sent by INUK owners. Al-Quran infaq (alms) verses are studied in depth through tafsir maudhui (thematic exegesis) to ensure the accuracy of the implementation of alms habits of Kudus residents. In contrast, the study's results serve as a basis for implementing the alms program at LAZISNU Kudus. This type of research is field research with a qualitative descriptive approach. Research data were obtained from LAZISNU documents, the INUK application, and interviews with LAZISNU leaders and INUK tin owners. The results of this study indicate that alms verses in the Quran have various meanings. The number of residents who donate through INUK and the funds they raise continue to increase. The main factor is the trust residents have built through the transparent and accountable use of funds. INUK tin holders can provide feedback and interact with LAZISNU via WhatsApp. This effort is effective in building trust and accountability of the alms funds. The contribution of this research is in the form of information on the appropriate and trustworthy use of funds managed by LAZISNU Kudus, and it provides evidence that small change, if pursued and managed well, can have a positive impact on the organization and the community.